2020
DOI: 10.1200/go.20.00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Access to Novel Drugs for Lymphoma and Chronic Lymphocytic Leukemia Between India and the United States

Abstract: This review will compare and contrast the costs and access to novel drugs for treating chronic lymphocytic leukemia (CLL) and lymphoma in the United States and India during the last 5 years. Clinical outcomes for patients with hematologic malignancies have improved significantly since the approval of immunotherapeutic and targeted therapies. These new treatments have had an impact on overall outcomes and have helped determine the design for translational research and future trials. Although most of these novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Unfortunately, access to the novel agents is currently limited to certain developed countries, and every effort should be made to make sure patients in developing countries also benefit from these outstanding drugs ( 12 ). Most novel drugs and targeted drugs approved by the US Food and Drug Administration (FDA) and marketed in the United States are not available in developing countries such as India ( 52 ). In a resource-limited hospital in Nigeria, the major first-line chemotherapy used was cyclophosphamide, vincristine, and prednisolone (CVP) for 42.9% of patients, followed by chlorambucil and prednisolone (CP) for 31.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, access to the novel agents is currently limited to certain developed countries, and every effort should be made to make sure patients in developing countries also benefit from these outstanding drugs ( 12 ). Most novel drugs and targeted drugs approved by the US Food and Drug Administration (FDA) and marketed in the United States are not available in developing countries such as India ( 52 ). In a resource-limited hospital in Nigeria, the major first-line chemotherapy used was cyclophosphamide, vincristine, and prednisolone (CVP) for 42.9% of patients, followed by chlorambucil and prednisolone (CP) for 31.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the survival rate of leukaemia cancer in children at different economic levels and countries is different due to the difference in treatment level, professional medical care, and malignant tumour prevention plan [31]. The development of drugs alleviates the death and DALY burden of leukaemia in the high SDI region [32]. Contrastingly, The DALY values for children in low SDI regions are much higher compared to those in high SDI regions.…”
Section: Childhood and Adolescent Leukaemia Burden In Different Regio...mentioning
confidence: 99%
“…The study identified various demographics which are at risk of conditions. V. Sathyanarayanan et al [ 14 ] did a comparative study of access to novel drugs for Lymphoma and Leukemia between USA and India. The study took different parameters into consideration before concluding that the treatment of the conditions has the same impact on quality of life and patient outcomes in both countries.…”
Section: Literature Reviewmentioning
confidence: 99%